An Exploration of Factors Impacting Preexposure Prophylaxis Eligibility and Access Among Syringe Exchange Users. Issue 4 (April 2018) - Roth, Alexis M.; Aumaier, Brenna L.; Felsher, Marisa A.; Welles, Seth L.; Martinez-Donate, Ana P.; Chavis, Martha; Van Der Pol, Barbara
Abstract : Background: In 2015, approximately 50, 000 new HIV infections occurred in the United States, 2, 400 of which were attributable to injection drug use. Preexposure prophylaxis (PrEP) has the potential to curb HIV acquisition; however, uptake remains low among persons who inject drugs (PWID). The purpose of the study is to describe PrEP eligibility, willingness to use PrEP, and ability to access PrEP among PWID recruited from a pilot program that paired screening and treatment of sexually transmitted infections with mobile syringe exchange program (SEP) services. Methods: Between 2015 and 2016, 138 PWID 18 years or older were recruited from a mobile SEP in Camden, New Jersey. Participants completed a survey assessing sociodemographics and HIV risk and underwent chlamydia and gonorrhea screening. Centers for Disease Control clinical guidelines were used to calculate PrEP eligibility. Differences by sex were examined using inferential statistics. Results: Most women (95.4%) and men (84.5%) were considered PrEP eligible ( P < 0.04). More women than men were willing to take PrEP (88.9% vs. 71.0%; P < 0.02). Participants reported substantial barriers to PrEP including feeling embarrassed (45.0%) or anxious (51.6%) about taking PrEP, nondisclosure to partners (51.4%), limited engagement with health care providers where PrEP might be provided (43.8%), and lacking health insurance (32.9%). Conclusions: Despite reporting behavior that warrants the use of PrEP to prevent HIV and finding the concept acceptable, PWID face multiple barriers to PrEP access. Without tailored interventions to promote PrEP, uptake will likely remain suboptimal. Packaging PrEP with SEP services could provide a viable option for reaching eligible and interested PWID. Abstract : A study of clients of a needle exchange in Camden, New Jersey, found that the syringe exchange programs are potential route for connecting eligible, high-risk clients to preexposure prophylaxis care.Supplemental digital content is available in the text.